2001
DOI: 10.1111/1467-9523.00171
|View full text |Cite
|
Sign up to set email alerts
|

The Farmer Within an Institutional Environment. Comparing Danish and Belgian Organic Farming

Abstract: This article is about variation in the expansion of organic farming sectors in different countries. It is suggested that variations in the absolute expansion of organic farming may be understood through a theoretical framework emphasizing the importance of the quality of the interrelationships among national institutions within organic farming as well as between organic and conventional agriculture. The theoretical proposition is illustrated by comparing the development in the institutional environment of orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 0 publications
1
31
0
Order By: Relevance
“…For the organic farming community, studies indicated that farmers' associations, advisory boards, and research institutions that offer training in organic agriculture improve organic practices through their support for farming management practices and organic marketing (Bloom and Duram 2007;Kroma 2006;Lynggard 2001;Nerbonne and Lentz 2003). When farmers shift from conventional to alternative systems of production, it reflects an interactive process in which groups of social actors develop practices and values that enable them to manage production systems in sustainable ways (Kroma 2006).…”
Section: The Structural-functional Perspectivementioning
confidence: 99%
“…For the organic farming community, studies indicated that farmers' associations, advisory boards, and research institutions that offer training in organic agriculture improve organic practices through their support for farming management practices and organic marketing (Bloom and Duram 2007;Kroma 2006;Lynggard 2001;Nerbonne and Lentz 2003). When farmers shift from conventional to alternative systems of production, it reflects an interactive process in which groups of social actors develop practices and values that enable them to manage production systems in sustainable ways (Kroma 2006).…”
Section: The Structural-functional Perspectivementioning
confidence: 99%
“…Institution operates at a variety of levels, and their elements can be embodied in and carried by cultures, by regimes and by formal organisations (Michelsen et al, 2001;Lynggaard, 2001). In fact, institutionalisation of family farms is a cultural process because the elements of family institutions originate from the family (e.g.…”
Section: Family As An Autonomous Institution For Local Agricultural Rmentioning
confidence: 99%
“…According to Lynggaard (2001), farmers' institutional environment has three different interfaces i.e. farmer/market, farmer/policy and farmer/farming systems.…”
Section: Family As An Autonomous Institution For Local Agricultural Rmentioning
confidence: 99%
See 2 more Smart Citations